PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 002 RAJA BEJAMU KECAMATAN SINABOI KABUPATEN ROKAN HILIR - Julina '; Zariul Antosa Zariul Antosa; Damanhuri Daud Damanhur Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research was motivated by the low student learning outcomes in social studies. From the daily tests carried only 9 students who have mastery (45%) whereas those who did not complete 11 (55%) with KKM 60 While the average student learning outcomes, namely 49.34. The form of this research is a form of Classroom Action Research (CAR), which aims to improve learning outcomes through the implementation of the IPS model of jigsaw cooperative learning in fourth grade Bejamu 002 King Rokan Hilir Subdistrict Sinaboi second semester of the school year 2013/2014 in the subject matter of economic activity in utilizing natural resources. The problem of this study are Is the application of the Jigsaw cooperative learning model to improve learning outcomes of students in social studies fourth grade Bejamu 002 King Rokan Hilir Subdistrict Sinaboi second semester of academic year 2013/2014 ?. The subjects were fourth grade students of SD Negeri Bejamu 002 King Rokan Hilir Subdistrict Sinaboi of 20 people consisting of 9 male students and 11 female students with academic and social abilities are heterogeneous. On the basis of students who achieve a score of KKM 9 people (45%), daily tests first 10 people (50%) and the second daily test increased to 19 people (95%). The average increase learning outcomes of basic score of 50.5 increased to 57 on daily tests I and 80.4 in the second daily test. The increased activity of teachers and students. In the first cycle with a percentage of 57% and 78% in the first and second meetings. While in the second cycle with the percentage of 82% and 100% in the first and second meetings. As for the activities of students in the first cycle 53% and 75% in the first and second meetings. While on the second cycle increased to 82% and 100% in the first and second meetings. Keyword : Cooperative Learning Model, Type Jigsaw, IPS Learning Outcomes